2023
DOI: 10.1080/07853890.2023.2203946
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modulations in cancer: predictive biomarkers and potential targets for overcoming the resistance to topoisomerase I inhibitors

Abstract: Introduction Altered epigenetic map is frequently observed in cancer and recent investigations have demonstrated a pertinent role of epigenetic modifications in the response to many anticancer drugs including the DNA damaging agents. Topoisomerase I (Top I) is a well-known nuclear enzyme that is critical for DNA function and cell survival and its inhibition causes DNA strand breaks and cell cycle arrest. Inhibitors of human Top I have proven to be a prosperous chemotherapeutic treatment for a vast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 136 publications
0
8
0
Order By: Relevance
“…The addition of acetyl groups, referred to as histone acetylation, serves to activate the corresponding chromosomal region, while their removal (deacetylation) leads to deactivation. Key enzymes in the regulation of gene expression are histone deacetylases (HDACs) [12,239].…”
Section: Epigenetic Changes and Topo-active Drugsmentioning
confidence: 99%
See 3 more Smart Citations
“…The addition of acetyl groups, referred to as histone acetylation, serves to activate the corresponding chromosomal region, while their removal (deacetylation) leads to deactivation. Key enzymes in the regulation of gene expression are histone deacetylases (HDACs) [12,239].…”
Section: Epigenetic Changes and Topo-active Drugsmentioning
confidence: 99%
“…Modification leading to hypomethylation can either increase or decrease the sensitivity of cells to topoisomerase inhibitors due to altered mechanisms. Also, it has been reported that the dysregulation of histone acetyltransferase (HAT) and histone deacetylases (HDACC), which play a key role in regulating the level of acetylation in histone proteins, results in resistance against topoisomerase inhibitors (Figure 4) [12,[248][249][250][251][252][253][254][255][256][257][258][259][260].…”
Section: Epigenetic Changes and Topo-active Drugsmentioning
confidence: 99%
See 2 more Smart Citations
“…Disruptions in epigenetic processes can lead to altered gene functions and cause cellular neoplastic transformation. The epigenetic modifications precede genetic changes and usually occur at the early stage of tumor development [119,120]. Among the epigenetic disorders in carcinogenesis, the most studied processes are the abovementioned ones, namely, gene promoter methylation, histone acetylation and methylation, changes in chromatin state, and expression of non-coding RNAs.…”
Section: Epigenetic Alterations In Carcinogenesismentioning
confidence: 99%